STRATEGI KEPALA MADRASAH TERHADAP PENINGKATAN KUALITAS SARANA DAN PRASARANA DI MADRASAH TSANAWIYAH NURUL IHSAN DESA BATIN KECAMATAN BAJUBANG KABUPATEN BATANG HARI - Wahdatul Istiqomah; Salahuddin Salahuddin; Suci Fitriani (STKIP Pesisir Selatan, 2026)
This study is motivated by the importance of educational facilities and infrastructure in supporting the quality of learning. However, the condition at Madrasah Tsanawiyah Nurul Ihsan, Batang Hari Regency, shows that the availability and feasibility of facilities and infrastructure are still not optimal and uneven. The main problem of this study is the strategy of the principal in improving the quality of educational facilities and infrastructure. This study aims to describe the condition of facilities and infrastructure, analyze the principal’s management strategies, and identify supporting and inhibiting factors. This research uses a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results show that facilities and infrastructure are relatively adequate but not optimal, especially in sports facilities, learning media, and supporting facilities. The principal’s strategies have been implemented participatively through planning, procurement, utilization, and maintenance, but weaknesses remain in inventory, storage. And disposal. Supporting factors include limited budgets, lack of practical facilities, and weak security systems.This study is motivated by the importance of educational facilities and infrastructure in supporting the quality of learning. However, the condition at Madrasah Tsanawiyah Nurul Ihsan, Batang Hari Regency, shows that the availability and feasibility of facilities and infrastructure are still not optimal and uneven. The main problem of this study is the strategy of the principal in improving the quality of educational facilities and infrastructure. This study aims to describe the condition of facilities and infrastructure, analyze the principal’s management strategies, and identify supporting and inhibiting factors. This research uses a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results show that facilities and infrastructure are relatively adequate but not optimal, especially in sports facilities, learning media, and supporting facilities. The principal’s strategies have been implemented participatively through planning, procurement, utilization, and maintenance, but weaknesses remain in inventory, storage. And disposal. Supporting factors include limited budgets, lack of practical facilities, and weak security systems.